How general is specific human capital? - Christina Gathmann; Uta Schönberg (Institute for the Study of Labor (IZA), 2006)
Previous studies assume that labor market skills are either fully general or specific to the firm. This paper uses patterns in mobility and wages to analyze how portable specific skills are in the labor market. The empirical analysis combines data on tasks performed in different jobs with a large panel on complete working histories and wages. Our results demonstrate that labor market skills are partially transferable across occupations. We find that individuals move to occupations with similar task requirements and that the distance of moves declines with time in the labor market. Further, tenure in the last occupation affects current wages, and the effect is stronger if the two occupations are similar. Our estimates suggest that task-specific human capital is the most important source of wage growth for university graduates. For the low- and medium-skilled, returns to task human capital are also sizeable, though smaller than for labor market experience.
urn:nbn:de:101:1-2008051347
Keywords: 330